Sonic hedgehog signaling pathway in vertebrate epithelial appendage morphogenesis: perspectives in development and evolution - Chuong*, C.-M. (Cell Mol Life Sci, 2000)
Vertebrate epithelial appendages are elaborate topological transformations of flat epithelia into complex organs that either protrude out of external (integument) and internal (oral cavity, gut) epithelia, or invaginate into the surrounding mesenchyme. Although they have specific structures and diverse functions, most epithelial appendages share similar developmental stages, including induction, morphogenesis, differentiation and cycling. The roles of the SHH pathway are analyzed in exemplary organs including feather, hair, tooth, tongue papilla, lung and foregut. SHH is not essential for induction and differentiation, but is involved heavily in morphogenetic processes including cell proliferation (size regulation), branching morphogenesis, mesenchymal condensation, fate determination (segmentation), polarizing activities and so on. Through differential activation of these processes by SHH in a spatiotemporal-specific fashion, organs of different shape and size are laid down. During evolution, new links of developmental pathways may occur and novel forms of epithelial appendages may emerge,upon which evolutionary selections can act. Sites of major variations have progressed from the body plan to the limb plan to the epithelial appendage plan. With its powerful morphogenetic activities, the SHH pathway would likely continue to play a major role in the evolution of novel epithelial appendages.